ANALISIS PENJELASAN FIQIH DARAH HAID METODE BUYA YAHYA TERHADAP PEMAHAMAN MAHASISWA FAKULTAS HUKUM UNIVERSITAS MUHAMMADIYAH KALIMANTAN TIMUR - Tsalis, Khodijah Nur; Pratama, Rio Arif; Jamal, Sri Wahyuni; Wulandari, Dewi; Piantari, Ni Komang Putri (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Understanding the fiqh of menstrual blood is very important for women, but not many formal schools teach menstrual blood material in Islamic religious studies. Though it is not easy to understand it because the menstrual blood cycle of each woman is different. This study aims to analyze the explanation of fiqh of menstrual blood in Buya Yahya's method and the basic knowledge of fiqh of menstrual blood on the understanding of UMKT Faculty of Law students. Buya Yahya's method in explaining the fiqh of menstrual blood is considered as one of the methods that is easy to understand. This research uses quantitative methods with data collection techniques used are questionnaires, with primary data sources, namely data obtained directly from the source through the distribution of forms. The data analysis technique used is multiple linear regression. The results showed that students understand the basic knowledge of fiqh of menstrual blood and the explanation of fiqh of menstrual blood in Buya Yahya's method.